Liquid-Liquid Phase Separation Phenomenon on Protein Sorting Within Chloroplasts - Zheng, Canhui; Xu, Xiumei; Zhang, Lixin; Lu, Dandan (Frontiers in Physiology, 2021)
In higher plants, chloroplasts are vital organelles possessing highly complex compartmentalization. As most chloroplast-located proteins are encoded in the nucleus and synthesized in the cytosol, the correct sorting of these proteins to appropriate compartments is critical for the proper functions of chloroplasts as well as plant survival. Nuclear-encoded chloroplast proteins are imported into stroma and further sorted to distinct compartments via different pathways. The proteins predicted to be sorted to the thylakoid lumen by the chloroplast twin arginine transport (cpTAT) pathway are shown to be facilitated by STTs driven liquid-liquid phase separation (LLPS). LLPS is a novel mechanism to facilitate the formation of membrane-less sub-cellular compartments and accelerate biochemical reactions temporally and spatially. In this review, we introduce the sorting mechanisms within chloroplasts, and briefly summarize the properties and significance of LLPS, with an emphasis on the novel function of LLPS in the sorting of cpTAT substrate proteins. We conclude with perspectives for the future research on chloroplast protein sorting and targeting mechanisms.